Italy in international relations : the foreign policy conundrum - Diodato, Emidio (Palgrave Macmillan, 2020)
Contents: Italy in International Relations; Acknowledgements; Contents; 1 Introduction; 2 Italy in International Relations: European Benchmark Dates and National Critical Junctures; 2.1 The European Understanding of the International System: A Proposed Set of Benchmark Dates; 2.2 A Diverging Country? Italy Through European Benchmark Dates and National Critical Junctures; 3 March 1861. The Challenging Myth of the Post-Imperial Legacy; 3.1 The (Re)birth of Italy in a Changing Europe; 3.2 Unified Italy: The Legacy of the Past and the Role of Foreign Policy. Contents: 3.3 The Myth Betrayed: The Collapse of Italian Foreign Policy4 September 1943. Democratic Transition and International Adjustment; 4.1 The Tragedy of Capitulation as a Critical Juncture; 4.2 Democratic Italy: A European Middle Power; 4.3 Italy in the Mediterranean: A Problematic (Re- )adjustment; 5 February 1992. Italy in a Post-Bipolar World; 5.1 The Republican Turn in the 1990s as a Near-Miss Critical Juncture; 5.2 The Changed Nature of the vincolo esterno; 5.3 A Middle power in Search of Itself; 6 Conclusion; Glossary; Bibliography; Index.